Frequency of diabetic retinopathy and its severity in type 2 diabetic patients with microalbuminuria - Bilal, Mohammad; Usman, Muhammad; Khan, Naeem; Khan, Kalim Ullah; Hanan, Adul (International Journal of Pathology, 2025)
Background: Diabetic retinopathy (DR) is a major microvascular complication of type 2 diabetes mellitus (T2DM) and a leading cause of vision loss. Microalbuminuria, an early marker of nephropathy, reflects generalized microvascular injury and may predict higher DR risk. This study aimed to determine the frequency of DR in T2DM patients with microalbuminuria.Methods: A comparative cross-sectional study was conducted at Qazi Hussain Ahmad Medical Complex, Nowshera, over 6 months. A total of 1,300 T2DM patients were screened for microalbuminuria by urine immunoturbidimetric assay. Patients with microalbuminuria (n=381) formed the study group, while an equal number of diabetics without microalbuminuria (n=381) served as controls. Exclusion criteria included prior retinal laser treatment, overt proteinuria or nephropathy of other etiology, and uncontrolled hypertension. All participants underwent detailed ophthalmic examination including fundoscopy by a consultant ophthalmologist. DR was graded as present or absent based on characteristic retinal lesions. Statistical analysis was performed using SPSS 25; Chi-square test determined associations, with p<0.05 significant. Results: Of 1,300 screened, 29.3% (381) had microalbuminuria. Their mean age was 52.4 ± 9.8 years, mean diabetes duration 10 ± 6 years, and 55% were male. DR was detected in 45.4% (173/381) of microalbuminuric patients compared with 24.3% (93/381) of normoalbuminuric controls (p<0.001). The relative risk of DR with microalbuminuria was 1.87 (95% CI 1.54–2.27). Vision-threatening DR occurred in 18% of the microalbuminuria group versus 7% of controls (p=0.002). Patients with microalbuminuria also had higher HbA1c (8.9% vs 8.1%, p=0.01) and longer diabetes duration (12 vs 8 years, p<0.001).Conclusion: Microalbuminuria is strongly associated with DR and may serve as a clinical indicator for heightened retinopathy risk. Regular ophthalmologic screening and improved glycemic control are essential in this high-risk subgroup.